Haematological parameters of three species of wild caught microchiropteran bats, Miniopteruschreibersii,Taphozousmelanopogon and Hipposideroslankadivain Sri Lanka - Ratnasooriya, W D; Udagama-Randeniya, P V; Yapa, W B; Digana, P M C B; Dharmasiri, M G (My University, 2005)
This study, for the first time in South Asia, examines hematological parameters of three different families having different global zoogeographical distributions; Miniopterus schreibersii (Vespertillionidae; n=12), Taphozous melanopogan (Emballonuridae; n=19) and Hipposiderous lankadiva (Hipposiderosidae; n=15). Blood samples were obtained from the median vein and the total white blood cells (WBC) count,red blood cell (RBC) count, packed cell volume (PCV), hemoglobin count (Hb), mean corpuscular volume (MCV) and mean corpscular hemoglobin content (MCHC) were determined using standard hematological techniques. Interspecies differences existed in some of the parameters monitored, i.e., PCV, MCV, WBC and RBC counts, % of neutrophils and lymphocytes. Onthe other hand, a gender discrepencywas recorded for T.melanopogon with respect to the total WBC count. The highestWBC count and the lowest pCV and MCV were found in M.scheibersii, T. melanopogon registered the highest percentage of lymphocyte and the lowest percentage of meutrophils, while H.lankadiva possessed the highest MCV. Hematological values were recorded also for a single lactating T.melanopogon.
Keywords: haematology; microchiroptera; Miniopterus schreibersii; Taphozous melanopogon; Hipposideros lankadiva